2005
DOI: 10.1051/forest:2005024
|View full text |Cite
|
Sign up to set email alerts
|

Leaf and whole-plant water relations of the Patagonian conifer Austrocedrus chilensis (D. Don) Pic. Ser. et Bizzarri: implications on its drought resistance capacity

Abstract: -Physiological studies have suggested that A. chilensis would survive during drought avoiding water stress through an early stomatal closure. However, there are no studies that have explored other potential mechanisms related to drought resistance or avoidance. The objectives were: (1) to measure hydraulic resistance, vulnerability to cavitation and leaf water relations, and (2) to compare these characteristics between different provenances. Pressure-volume curves demonstrate that A. chilensis has high osmotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 22 publications
5
18
0
2
Order By: Relevance
“…However, the low but positive rates of photosynthesis at low stomatal conductances are similar to data reported for several Cedrus and Quercus species (Epron 1997, Fotelli et al 2000, two Mediterranean species able to survive during periodic droughts. Hydraulic resistance measured in whole plants and their compounds showed that the main resistance to water flow in A. chilensis is located at the leaf level (Gyenge et al 2005). Based on these results, it appears that the strategy of A. chilensis seedlings is to sustain favorable water conditions during a drought, by maintaining relatively high water potential by means of an early stomata closure (desiccation avoidance response).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, the low but positive rates of photosynthesis at low stomatal conductances are similar to data reported for several Cedrus and Quercus species (Epron 1997, Fotelli et al 2000, two Mediterranean species able to survive during periodic droughts. Hydraulic resistance measured in whole plants and their compounds showed that the main resistance to water flow in A. chilensis is located at the leaf level (Gyenge et al 2005). Based on these results, it appears that the strategy of A. chilensis seedlings is to sustain favorable water conditions during a drought, by maintaining relatively high water potential by means of an early stomata closure (desiccation avoidance response).…”
Section: Discussionmentioning
confidence: 75%
“…In addition, high radiation and temperature could damage photosynthetic apparatus when stomata are closed (Epron 1997). Gyenge et al (2005) found that seedlings of A. chilensis had high total plant resistance, with more than 70% of their water hydraulic resistance placed at leaf level. These could imply a low capacity to transport water from the soil to the leaf.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated ontogenetic shifts for functional traits such as biomass allocation, SLA or A for tropical [36,43,53] or temperate (e.g. [11]) species, whereas no such shift was observed for hydraulic traits for Patagonian conifers [27]. Our results support the statement that among species differences in the metabolic intrinsic set point for the trade-off between carbon and water fluxes at the leaf level, as reflected by ∆ [13], are maintained over the lifetime of these species.…”
Section: Functional Diversitymentioning
confidence: 99%
“…But sometimes, species with a broad geographical distribution does not show physiological variability [17]. Differences in the osmotic adjustment capacity were observed among provenances of several Eucalyptus [25,42], between and within subspecies of E. globulus [15,54], as well as among clones of E. globulus subsp.…”
Section: Provenance Differencesmentioning
confidence: 99%